On the monotonicity and constancy of signs of some rational explicit methods for nonlinear systems of ordinary differential equations - Hlynsky, Ya.M.; Panchyshyn, Yu.Yu. (Український математичний журнал, 1995)
We study one special type of explicit rational numerical methods for the solution nonlinear systems of ordinary differential equations and analyze the so-called property of constancy of signs of integration methods. This means that the inner product of approximate solutions at two adjacent points of the grid is positive for the corresponding differential equation. We establish the unconditional (i.e., for all sizes of steps) monotonicity and constancy of signs of rational methods. Вивчається один тип числових дробово-раціональних явних методів для розв’язування нелінійних систем звичайних диференціальних рівнянь. Розглядається властивість знакосталості методу інтегрування. Зпакосталісгь означає, що скалярний добуток наближених розв’язків, взятих у двох сусідніх точках сітки, є додатним для відповідного диференціального рівняння. Доведено безумовну (для всіх значень кроку) монотонність і зиакосталість дробово-раціональних методів.